PENGARUH SKEPTISME PROFESIONAL DAN PENGALAMAN AUDITOR TERHADAP KEMAMPUAN AUDITOR EKSTERNAL DALAM MENDETEKSI KECURANGAN (SURVEI PADA AUDITOR BPK RI PERWAKILAN SULAWESI UTARA) - Mokoagouw, Monica; Kalangi, Lintje; Gerungai, Natalia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
External auditor is an independent and competent person who can examine financial statements and be responsible for the opinions given. This research aims to examine the effect of professional skepticism and auditor’s experience on fraud detection ability of external auditor. The sample in this research are all auditors who work in Badan Pemeriksa Keuangan (BPK) Republik Indonesia (The Indonesia’s Supreme Audit Institution) Reprensentative of North Sulawesi Province. The data of this research is using primary data. The data was collected  by distributing  questionnaires directly to auditors of BPK RI Representative of North Sulawesi Province. This research is using the multiple linear regression analsys with SPSS 23.  The result indicate that: 1) Professional Skepticism has positive effect towards Fraud Detection Ability of External Auditor. 2) Auditor’s Experience has positive effect towards Fraud Detection Ability of External Auditor. 3) Professional Skepticism and Auditor’s Experience simultaneously have positive effect towards Fraud Detection Ability of External Auditor. Keywords: Professional Skepticism, Auditor’s experience, Fraud Detection Ability of External Auditor